Gambaran Pembinaan oleh Pendamping Program Terhadap Anggota Permodalan Nasional Madani di Berok Siteba Kota Padang - Berlianda Putri, Marni; Syur’aini, Syur’aini (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is motivated by the success of members in opening a business in the Permodalan Nasional Madani Program Mekaar in Berok Siteba Kota Padang. The researcher suspects that the high success achieved by the training members, is influenced by the high level of guidance provided by the program's facilitator to the training members in knitting the PNM program mekaar in Berok Siteba Kota Padang. This can be seen from the guidance given in guiding, developing and supervising the knitting training members. This study aims to describe the guidance given by program facilitators to PNM members of the Mekaar Program in Berok Siteba. This type of research is quantitative descriptive research. The population in this study were 20 members of the PNM Program Knitting Training. The sampling technique used was a census, all populations were sampled 20 people. Data collection techniques using a questionnaire in the form of a Likert Scale. While the data analysis technique uses the percentage formula. From the results of the study it was found that: (1) the coaching provided by the program assistant in the aspect of guidance was categorized as good, (2) the coaching provided by the program facilitator in the development aspect was categorized as good, (3) the coaching provided by the program facilitator in the supervision aspect was categorized as good. Based on the results of the study it is recommended that members of the PNM knitting training program can always bring changes to a better direction and can give examples to new members who join the program in opening a business and to program companions can always foster members well and continue to motivate members in developing knowledge, attitude and skills